Yoga bitch : one woman's quest to conquer skepticism, cynicism, and cigarettes on the path to enlightenment - Morrison, Suzanne (Three Rivers Press, 2011)
"When Suzanne Morrison decides to travel to Bali for a two-month yoga retreat, she wants nothing more than to be transformed from a twenty-five-year-old with a crippling fear of death into her enchanting yoga teacher, Indra--a woman who seems to have found it all: love, self, and God. But things don't go quite as expected."--Page 4 of cover.